Sinergi Pemasaran dan Pengelolaan Keuangan dalam Katalis Kepercayaan Masyarakat pada Yayasan Pendidikan Tajaul Karomatu Kabupaten Tangerang - Amanda Rizkyani; Hanifah Septiani; Muhammad Ponco; Fitri Sabina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Public trust is a crucial factor in supporting the sustainability and development of educational institutions. In educational foundations, effective marketing strategies and sound financial management play important roles in enhancing institutional credibility and strengthening stakeholder confidence. Therefore, community service activities were conducted at Tajaul Karomatu Educational Foundation, Tangerang Regency, to improve participants’ understanding of marketing and financial management as catalysts for public trust. The purpose of this Community Service Program (PKM) was to enhance the knowledge and skills of teachers and staff regarding integrated marketing strategies and transparent financial management practices to support institutional development and community confidence. The activity was carried out on August 31, 2025, at Tajaul Karomatu Educational Foundation. The PKM team consisted of three lecturers from Pamulang University, involving 20 participants comprising teachers and administrative staff. The implementation method included three stages: preparation, implementation, and reporting. During the implementation stage, activities were conducted through material presentations, practical exercises, discussions, and question-and-answer sessions to encourage participant engagement and understanding. The results showed an increase in participants’ awareness of the importance of strategic marketing and accountable financial management in building public trust. Participants demonstrated improved understanding of promotional planning, financial recording, transparency, and accountability practices. The activity also fostered greater readiness among teachers and staff to apply these concepts in supporting the foundation’s institutional performance and reputation.